SYNCHRONOUS ARABIC LEARNING BASED ON SOCIOCULTURAL THEORY: NEW TRENDS IN ARABIC LEARNING AT UNIVERSITY - Maimunah, Iffat; Sutaman, Sutaman; Taufiqurrochman, R.; Siregar, Husnatul Hamidiyyah; Alaoui, Moulay Mhamed Ismaili (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This paper aims to analyze the implications that arise from virtual learning spaces built through synchronous Arabic learning by video conference to find out the supporting factors for the success of learning. This study uses three data collection techniques: observation, interviews, and documentation. The analysis of the data that has been collected is carried out to produce accurate data following the existing data and facts. The data analysis technique was passed through three processes, namely (1) restatement of data collected according to each theme, (2) description, and this technique was carried out to find data patterns and trends, and (3) interpretation, the purpose of using this technique. The research results show the importance of revolution and transformation of language learning from the classical conditioning approach to social constructivism. This pattern shift can also change dependence on technology, shown in the effectiveness of learning that will run with the affordability of computer and internet media support.